Dominant factors on selection of contraception toward new family planning acceptors in public health center area in Padang - Rahmatiqa, Chamy; Patricia, Helena (International Journal Of Community Medicine And Public Health, 2020)
Background: The use of family planning or as known as KB in Indonesia from 1970 to 2017 has increased significantly. The most use of KB in non MKJP was injection 70% and pill 21%. The use of this method was very influential on the level of family planning continuity. Viewed from the 2012 SDKI, the dropout rate in the injection method was 40.7%. This phenomenon has contributed to the stagnation of the total fertility rate and ultimately still impact to the high maternal mortality rate in Indonesia. Methods: This analytic study was conducted with a cross sectional approach. The populations in this study were all new family planning acceptors and samples of 114 people were taken by random sampling technique. The data collection was a questionnaire with data analysis using chi-square test. Results: More types of contraception were non MKJP (66.4%), more early adult age (60.8%), education level was more than half of low education (54.4%), and most of the mothers were unemployed (76.8). The parity were more than 1 and 2 children (52.8%), more contraceptive goals who did not want their children (60%), and the low support of their husbands was more than the high support of their husbands (55%). There was a relationship between age, education level, work status, parity, contraceptive goals, and husband support with the selection of contraceptive methods in new family planning acceptors. Conclusions: The dominant factor on selection of contraception toward new family planning acceptors was husband support.